(untitled) (Acta Scientiarum. Animal Sciences, 2019)
An experiment with Leghorn laying hens was undertaken to determine the effect of oyster shell particle size and feeding time on different production variables, calcium retention, plasma calcium content and egg internal and external quality. Two hundred Leghorn layers (40 weeks old old) were allocated in five dietary treatments with four replicates during ten weeks. Two particle size combinations (wherein 50% of calcium substituted by medium or coarse particles (1-2 mmand 2-4 mmrespectively) and two feeding time (8-pm or 9-am) were compared against a control diet (100% ground, <1 mmwhich fed with meal). Egg number, egg production, egg mass and feed conversion ratio did not differ among treatments (p > 0.05). Hens fed diets containing coarse Ca had significantly greater feed intake and calcium content of excreta (p > 0.05), whereas medium particle size reduced feed intake compared to control. Coarse particle size and feeding time at 9-pm significantly increased the calcium content of egg shell, egg shell thickness, egg surface area (ESA) and shell weight per unit surface area (SWUSA) (p < 0.05). Plasma calcium concentration, gizzard digesta calcium content and egg specific gravity were not affected by treatments (p > 0.05). Providing of calcium at 9-pm resulted an increase of egg shell (%), shell weight and thickness (p < 0.05). The results have shown that substitution of fine oyster shell with 50% coarse particles (2-4 mm) and feeding time at 9-pm have better effects on egg shell quality.